Characterization of banana peel ionic polymer membrane by using polynomial regression. (2021) - Raturi, Poonam; Panwar, Varij; Singh, Sumeshwar
Abstract: The banana peel contains Phenolic compounds, which has higher concentrations as compared to other fruits. These Phenolic compounds contain very rich concentration of antioxidant, antimicrobial and antibiotic properties. The amendment of banana is good in India as well as world. The banana has second main fruit crop in India. The Banana has belong to Musa family. It is grown in warmer areas. Banana contains potassium, vitamin B6, vitamin C and various antioxidants and phytonutrients. Alike the banana peel (BP) contains Iron, cadmium, chromium, Nickel, Copper, lead and Zinc conducting materials. By using conducting material a flexible conducting ionic polymer membrane developed. The purpose of this paper is optimum use of the nutrients which is present in banana peel (Bp). Banana peel is biodegradable material, when they get some moisture its get starts rotten which increased the production of the micro-organism, causes disease. Through banana peel an ionic polymer membrane is developed which helps overcome the banana peel waste problem. Through impedance analyzer we measured the electrical property of the banana peel ionic polymer membrane. Electric properties like conductance, capacitance, real and imaginary impedances are measured. From 20 Hz to 10 mHz range frequency is used to measure all electric properties. By using this range different- different 1600 / electric values are calculate. All these values are plotted with the help of polynomials regression. The conductivity PVA/BP is enhanced from 3 X 10 -8 S to 8 X 10 -7 S by increasing the concentration of banana peel from 1 ml to 4 ml. The composition BP/ PAV shows good conduction or low dissipation factor and low dielectric constant.